Estrategias Urbano - paisajistas que permitan consolidar el borde del municipio de Candelaria – Valle del Cauca. - Viáfara Pinillos, Jefferson; Pantoja Sinisterra, Manuel Alejandro (Universidad Antonio Nariño, 2023)
As time goes by, architecture cont fundamentals to progress to levels beyond architectural elements, positioning itself in society as an important branch in the social, cultural, and economic fields, among others, of a territory.